DYNAMICS IN MEDICAL TREATMENT OF ISCHEMIC HEART DISEASE IN CLINICAL PRACTICE - S. A. Shalnova; A. D. Deev; S. A. Boytsov (Столичная издательская компания, 2015)
At the present time ischemic heart disease (IHD) continues to be the leading cause of cardiovascular mortality. Improvement of treatment methods is an important aspect in reduction of IHD fatal complications. Aim. To carry out a meta-analysis of several clinical and epidemiological studies with research on the use of drugs with established prognostic effect in patients with IHD. Material and methods. Analysis of dynamics in drug prescription in IHD was conducted based on Russian clinical and epidemiological trials, performed from 2004 to 2009 years. Results. The total amount of patients was 17345. Majority of them suffered from arterial hypertension (81.6%), one third had a history of myocardial infarction, more than a half revealed heart failure (59.8%). At that history of diabetes mellitus was only registered in 10.5% of the patients varying from 8% to 17.6%. Lipid metabolism disorders were present in more than a half of the patients. On the average one in four patients was obese. At drug therapy analysis it was found out that 6.4% of the IHD patients received no medications. Statins intake increased from 5.3% to 85.7% in men and from 9.6% to 69.3% in women in last 5 years. Incidence of the renin-angiotensin-aldosterone system blockers intake increased by 13% in the both genders. Men with IHD received antiplatelet agents more often than women. So, only 45.9% of women received these drugs in 2004 and 57.9% in 2009, while men increased antiplatelet agents use from 58.5% in 2004 to 63.5% in 2009. Men received beta-block- ers by 14% more often in 2009 (74.6%) than in 2004 and women - by 30% (82.4%). Conclusion. The incidence of the prescription of the drugs with established prognostic value has increased recently. At that rate of IHD mortality in cardiovascular mortality structure continues to be high probably due to inadequate treatment. First, the number of coronary surgical interventions in our patients is significantly lower than in the other countries. Second, despite con- siderable increase in the drug use, doses and adherence to treatment remain insufficient. Representative trials with participation of different-level healthcare institutions are reasonable.